Availability of food and beverage items on school canteen menus and association with items purchased by children of primary-school age. Issue 15 (2nd August 2018) - Clinton-McHarg, Tara; Janssen, Lisa; Delaney, Tessa; Reilly, Kathryn; Regan, Tim; Nathan, Nicole; Wiggers, John; Yoong, Sze Lin; Wyse, Rebecca; Grady, Alice; Lecathelinais, Christophe; Wolfenden, Luke
Abstract: Objective: To (i) describe the proportion of foods and beverages available on school canteen menus classified as having high ('green'), moderate ('amber') or low ('red') nutritional value; (ii) describe the proportion of these items purchased by students; and (iii) examine the association between food and beverage availability on school canteen menus and food and beverage purchasing by students. Design: A cross-sectional study was conducted as part of a larger randomised controlled trial (RCT). Setting: A nested sample of fifty randomly selected government schools from the Hunter New England region of New South Wales, Australia, who had participated in an RCT of an intervention to improve the availability of healthy foods sold from school canteens, was approached to participate. Subjects: School principals, canteen managers and students. Results: The average proportion of green, amber and red items available on menus was 47·9, 47·4 and 4·7 %, respectively. The average proportion of green, amber and red items purchased by students was 30·1, 61·8 and 8·1 %, respectively. There was a significant positive relationship between the availability and purchasing of green ( R 2 =0·66), amber ( R 2 =0·57) and red menu items ( R 2 =0·61). In each case, a 1 % increase in the availability of items in these categories was associated with a 1·21, 1·35 and 1·67 % increase in purchasing of items of high, moderate and low nutritional value, respectively. Conclusions: The findings provide support for school-based policies to improve the relative availability of healthy foods for sale in these settings.